Analisis Kinerja KPU Kota Medan Dalam Menyusun Pendaftaran Panitia Pemilihan Kecamatan (PPK) untuk Pemilu 2024 - Batubara, Annisa ismaida; Tambunan, Reza Syahputra; Adzan, Muhammad; Andrean, Wiki Helmi; Arifinsyah, Arifinsyah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Indonesia is a democratic country that considers elections to be a benchmark in democracy. One form of democracy in Indonesia, for example, is holding elections to represent the voices of the people. The existence of the KPU as an election organizer is also required to be professional, accountable and have high integrity, because it has a very important strategic value. To assist the KPU in holding general elections, JUBERJURDIL requires members of the District Election Committee (PPK). The method used in this study is to use qualitative methods by using observation, interviews and documentation as data collection techniques. The results of this study indicate that the performance of the Medan City KPU in compiling the registration of the sub-district election committee (PPK) for the 2024 elections has been fairly good. The General Election Commission was formed in order to assist the KPU to carry out elections in 2024 in an orderly manner. Medan City KPU invites Medan City residents to register themselves to become members of the Medan City PPK. Keywords: Performance, KPU, PPK, Election